Klein-Gordon Oscillator in the Presence of External Fields in a Cosmic Space-Time with a Space-Like Dislocation and Aharonov-Bohm Effect - Faizuddin Ahmed (Advances in High Energy Physics)
In this paper, we study interactions of a scalar particle with electromagnetic potential in the background space-time generated by a cosmic string with a space-like dislocation. We solve the Klein-Gordon oscillator in the presence of external fields including an internal magnetic flux field and analyze the analogue effect to the Aharonov-Bohm effect for bound states. We extend this analysis subject to a Cornell-type scalar potential and observe the effects on the relativistic energy eigenvalue and eigenfunction.